Risk of Middle Ear Complications in Intubated Patients on Mechanical Ventilation Versus Non Intubated - Elfleleh , Salem (Scientific Journal of University of Benghazi, 2020)
Patients on mechanical ventilation through artificial airway intubation may compromise their normal eustachian tube function and equilibration of middle ear pressures. Aim of the study is to evaluate the risk of middle ear complications in the positive pressure air-filled middle ears. A prospective study of patients findings with a different diagnosis, who were admitted for more than ten days duration in Intensive Care Units (ICU) in different hospitals of Benghazi city over a period of six months . Head injury and tympanic membrane rupture were excluded in this study. The approach that had been used was otoscope examination of the ears of 120 ICU patients by an ENT specialist, Results: (the age ranged from 14 days to 75 years). The comparison between two groups of intubated (40 cases) and non-intubated (80 cases) patients was performed. Among 40 mechanically ventilated patients, 37 patients (92.5%) developed middle ear complications. Whereas only nine out of 80 patients in non intubated group(11.3%) were developed middle ear complications. These results suggest that all intubated patients on mechanical ventilation for more than ten days should be routinely examined, and subjected for portable tympanometry evaluation of the middle ear. They may need tympanostomy tubes insertion.